THE INFLUENCE OF ITS OWN STRESSES ON CONCRETE STRENGTH UNDER COMPRESSING - Fenko, О.; Krupchenko, O.; Yurko, I. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of experimental studies of the impact own stress unevenly distributed over the cross section, for strength of brittle materials were presented. Changes in the distribution of stresses in own cross-section caused by uneven shrinkage of concrete samples were analyzed. The reasons for own impact stresses are unevenly distributed over the cross-sectional sample for strength of concrete compressive were justified. Also the effects of stress on its own strength of concrete at its moisture were considered. Described impact on own stress compressive strength is confirmed by experimental results obtained by other authors. Shows the distribution of stresses in its own cross section at its water saturation and drying is not only concrete and also other porous materials. Keywords: own stresses, strength of concrete, water saturated concrete, shrinkage, creep.